PS02.040: EXPRESSION OF INTESTINAL/NON-INTESTINAL DIFFERENTIATION MARKERS IN ADENOCARCINOMAS OF THE ESOPHAGUS CORRELATES WITH ESOPHAGO-GASTRIC INTESTINAL METAPLASIA. (14th September 2018) - Bonora, Elena; Isidori, Federica; Lugaresi, Marialuisa; Sala, Claudia; Malvi, Deborah; Fittipaldi, Silvia; Castellani, Gastone; Räsänen, Jari; D'Errico, Antonietta; Fiocca, Roberto; Mattioli, Sandro
Abstract: Background: Esophageal adenocarcinomas (EAC), grouped according to the presence (+ )/absence (-) of intestinal metaplasia in esophagus (BIM) and stomach (GIM) differ in terms of nodal metastatic patterns and survival. We studied the differentiation profile in BIM/GIM categories. Methods: In 77 EAC surgical specimens we assessed CDX-2, CK7, CK20, MUC1, MUC2, MUC5A/C, MUC6 antibodies. The expression of such markers was correlated with: BIM + GIM- (Barrett-like), BIM-GIM- (cardiopyloric-like), BIM-GIM + (gastric-like). Results: CDX2 ( P = 0.0481), CK7 ( P = 0.0150), MUC2 ( P = 0.0395) were differently expressed (Kruskall-Wallis test) in BIM/GIM categories. Binary relations (Mann-Whitney test) showed that CDX2 was more expressed in BIM + /GIM- than in BIM-/GIM- ( P = 0.0046) tumors; CK7 was more expressed in BIM-/GIM- than in BIM-/GIM + ( P = 0.0020) and in BIM + /GIM- than in BIM-/GIM + ( P = 0.0101); MUC2 was more expressed in BIM + /GIM- than in BIM-/GIM- ( P = 0.0061). The other investigated markers were randomly distributed among BIM/GIM categories. Conclusion: The greater expression of intestinal markers (CDX2-MUC2) in Barrett's intestinal metaplasia associated tumors (BIM + /GIM-) compared to those with no intestinal metaplasia (BIM-/GIM-) is consistent with their predominant intestinal differentiation. In contrast, CK7, although mostly expressed in tumors not associated with intestinal metaplasia (BIM-/GIM-) was less efficient in distinguishing them from those associated with Barrett's metaplasia (BIM + /GIM-) while showed the lowest level of expression in tumors associated with gastric intestinal metaplasia (BIM-/GIM + ). In conclusion, intestinal (CDX2-MUC2) and non-intestinal (CK7) differentiation markers appear to be expressed differently in BIM/GIM categories. Those findings support the opportunity to investigate further biology of these tumors in view of clinical-prognostic implications. Disclosure: All authors have declared no conflicts of interest.